(untitled) (CIPEEX, 2023)
THE ARTICLE DISCUSSES THE HISTORY AND EVOLUTION OF ENVIRONMENTAL PROTECTION AREAS (EPAS) IN BRAZIL, INSPIRED BY FRENCH AND PORTUGUESE MODELS, EMERGING IN THE 1980S. ENVIRONMENTAL LEGISLATION, INCLUDING THE NATIONAL SYSTEM OF NATURE CONSERVATION UNITS (SNUC), IS ADDRESSED AS A CRUCIAL TOOL FOR THE PROTECTION AND MANAGEMENT OF EPAS. THE METHODOLOGY EMPLOYED A SYSTEMATIC LITERATURE REVIEW, ENCOMPASSING SCIENTIFIC ARTICLES AND TECHNICAL DOCUMENTS. THE RESULTS HIGHLIGHT CHALLENGES SUCH AS TERRITORIAL CONFLICTS, INAPPROPRIATE LAND USE, AND A LACK OF EFFICIENT MANAGEMENT, INCLUDING MANAGEMENT PLANS AND GOVERNING COUNCILS. THE NEED FOR URGENT MEASURES TO STRENGTHEN MANAGEMENT, INVEST IN ENFORCEMENT, AND PROMOTE SOCIAL PARTICIPATION IS EMPHASIZED, ENSURING THE EFFECTIVENESS OF EPAS IN CONSERVING BRAZIL’S NATURAL RESOURCES.